Mentha piperita essential oils loaded in a chitosan nanogel with inhibitory effect on biofilm formation against S. mutans on the dental surface. (15th May 2019) - Ashrafi, Behnam; Rashidipour, Marzieh; Marzban, Abdolrazagh; Soroush, Setareh; Azadpour, Mojgan; Delfani, Somayeh; Ramak, Parvin
Graphical abstract: Highlights: Mentha piperita essential oils was successfully loaded in a chitosan polymeric nanogel. MPEO-nanogel was effective in biofilm inhibition against Streptococcus mutans . Biofilm formation by S. mutans on the dental surface efficiently decreased in the presence of MPEO-nanogel. Biofilm related genes was significantly downregulated in the presence of MPEO-nanogel. Abstract: Mentha piperita essential oils (MPEO) were loaded into chitosan nanogel to use as antibiofilm agent against Streptococcus mutans and to protect its dental plaque. Chitosan nanoparticles (CsNPs) were prepared by sol-gel method using linking bridge of tripolyphosphate (TPP). Physiological properties of MPEO-CNs were assessed by FTIR, SEM/EDX, DLS and zeta potential. Release kinetics, MIC and MBC were determined for MPEO-CNs. Expression of biofilm-associated genes including 8 genes: grf B, C and D, brp A, spa P, gbp B, rel A and vic R was investigated at the presence of sub-MIC of MPEO-CNs. Most abundant bioactive compounds of MPEO were l-menthol (45.05%) and l-menthal (17.53%). SEM/EDX exhibited successful entrapment of MPEO into CsNPs followed by the changes in abundance of elemental peaks. A signal at 1737 cm −1 on chitosan spectrum was attributed to the carboxylic (CO) groups overlapped by MPEO incorporation. A new signal at 2361 cm −1 was assigned to electrostatic interactions of amine groups in chitosan with phosphoric units of TPP within the MPEO-chitosan. MPEO incorporation into porous nanogel decreased monodispersity of the nanoparticles and then raises z-average. Maximum release of MPEO was about 50% during 360 h in a hydroalcoholic solvent at ambient temperature. The adherence of bacterial cells showed high sensitivity to the nanoformulation of MPEO compared with unloaded chitosan-nanogel. Antibiofilm inhibition of S. mutans occurred in 50 and 400 μg/mL for MPEO-CNs and unloaded-nanogel, respectively. Among biofilm synthesis genes, gtf B, gtf C, gtf D were slightly affected by MPEO-CNs treatment, while gbp B, spa P, brp A, rel A, and vic R genes underwent significant down-regulation in the presence of both unloaded-nanogel and MPEO-loaded-nanogel. This study demonstrated that the MPEO-CNs promised an efficient nanoformulation with the greatest inhibitory action against some glycosyltransferase genes ( gtf B, C and D) as important enzymes involved in extracellular polymers. Finally, the results concluded that MPEO-CNs have a potential use as antibiofilm agent in toothpaste or mouth washing formulations.